Penerapan Pembelajaran Model Inquiry Based Learning untuk Meningkatan Hasil Belajar IPS Materi Perubahan Sosial Budaya Siswa Kelas IXC SMPN 3 Pamekasan - Tiwuk Susanti (IAIN Madura, 2020)
The research aims to describe the process and learning outcome in clss IXC SMPN 3 Pamekasan. This study uses classroom action research which id devided into 2 cycles. Each cycle is carried out through 4 stages, namelly planing, implementation, fobservation and reflection. The results showed that the application of the inquiry-based learning model has provided higher learning outcomes in class IXC students of SMPN 3 Pamekasan, this can be seen from the results of tests conducted by researchers namely the average class 67 in the first cycle, increasing to 76 in the second cycle with a success rate 53% increasing to 67%. In the practice of lerning, students are more active and concentrated when doing identification activities, students think critically in concluding the Social and Cultural Change well, and researchers can play an active role and guiding students in activities. Based on theresults of the study, it can be concludedthat the inquiry based learning model can improve learning outcomes identifying Cultural Changes in the IXC students of SMPN 3 Pamekasan.